Education, Future, and the Archipelago : Educational choice and post secondary views among young Swedish language vocational education students in the Finnish archipelago - Peltomäki, Olivia (My University, 2026)
Vocational Education and Training (VET) is the backbone of the Finnish workforce, educating more than 250,000 people last year. The high percentage of students who choose VET as their option for continuing their education warrants a review of where vocational school is available, and how the availability impacts students’ agency in transitioning from basic education and onwards. The archipelago is in a unique position compared to mainland Finland, with no local offerings in the middle and outer archipelago. Students who attend VET must either commute or board in the mainland. Ten students from the archipelago currently studying VET in the mainland were interviewed, the goal was to ascertain the student’s perception of choice and accessibility in obtaining upper secondary compulsory education. This study analyses the concept of choice through the Bourdieusian Social Choice Theory which views that people’s views on educational decision making and values is based off of collective impressionable experiences, in this context the archipelago. Ten Swedish speaking VET students were interviewed, Archers 3 stage analysis was used in the analysis of the interviews with the construction of a “Structural Domain” and “Cultural Domain” through which experiences can be categorized. Analysis revealed that choice in education is something not thought about in practical terms, students opted for the closest option to them as going further away to other areas of Finland would mean that they would have less opportunity to remain connected to their family in the archipelago. Students also described that due to the limited number of Swedish language instructions available that they did not think about choice in education. Students were also cautious about the thoughts of the future, economic uncertainty and challenges related to a lack of Finnish language skills proved unnerving for some. Overwhelmingly related to the future students believed that there is a type of preset path for them, graduate and get a job, outside of that there was little view of what the future could hold for them. Overall students, although satisfied with their current studies, were aware of the concept of spatial inequality in terms of educational accessibility compared to students in the mainland and agreed that there are limitations to the education offered.
Keywords: VET, Rural education, Youth studies, Finnish education, educational choice